Impact of Project Based Learning (PjBL) on Enhancing Student Self-Confidence - Jeihan Numalita Aghra Tia; Muhammad Nur Wangid (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study focuses on the issue of students' lack of self-confidence. Many students are hesitant to voice their opinions or ask questions during class, unsure of their abilities, likely to copy answers from peers, afraid of tests, and nervous when performing in front of others. The study employed quasi-experimental design with two fifth-grade classes: 20 students from MI Sultan Agung and 20 students from Caturtunggal State Elementary School 4 in Yogyakarta. Descriptive statistics and hypothesis testing (independent sample test and paired sample test ) were used to analyze the data. The findings show that the Project Based Learning (PjBL) paradigm significantly improves primary school students' self-confidence. The paired t-test results showed a t-value of 17.888 and a significance level of 0.000 (p 0.05), suggesting that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This suggests that PjBL is more effective than conventional learning methods in boosting students' self-confidence.